Disruption of Fis reduces bacterial persister formation by regulating glutamate metabolism in Salmonella. (March 2021) - Yan, Dongmei; Zhang, Qisi; Fu, Qingping; Sun, Mingzhong; Huang, Xinxiang
Abstract: The presence of persisters causes recalcitrance to antibiotic treatment, and can be attributed to a fairly large number of clinically refractory infections in several species of bacteria. Many studies have explored this phenomenon, but the mechanisms remain poorly understood. In this study, we found that the deletion of fis, which encodes a key DNA-binding protein mediating various biological processes, significantly reduced persister formation in S . Typhi. Persister assays and glutamate determination analysis showed that Fis mediated Salmonella persistence through regulating glutamate metabolism. Additionally, glutamate incubation altered the expression of the stringent response regulatory genes, demonstrating that the stringent response was related to glutamate regulation by Fis. The findings revealed that glutamate metabolism regulated by Fis serves as a mechanism for persister formation in S . Typhi. Highlights: The global regulator Fis is beneficial for persister formation in S. Typhi. Glutamate metabolism regulated by Fis is contributed to the persistence of S. Typhi. Persistence regulated by Fis may have a link with the stringent response in S. Typhi.